METHODOLOGICAL CHARACTERISTICS OF FORMING STUDENTS’ INFORMATION CULTURE - Sobirov Dilshod Solayevich (PEDAGOGS, 2024)
Annotation: Today, information technology in the field of education is one of the important factors of imparting knowledge to students and young people.  This article provides information on methodological features of forming students’ information culture.